(untitled) (Student’s Journal of Health Research Africa, 2024)
Background Epidermal inclusion cysts (EIC) are the most common cutaneous cysts and can occur anywhere on the body. These cysts can occur anywhere on the body, typically present as nodules directly underneath the patient’s skin, and often have a visible central punctum. It commonly results from the trauma to the pilosebaceous unit in the hair-bearing area. In areas without hair, these cysts are considered implantation and proliferation of squamous epithelium into the dermis due to injury. Objective It is to evaluate the clinicopathologic details of the usual and unusual sites of the epidermoid cyst. Material & Method Patients of epidermal inclusion cysts encountered over 1 year from January 2023 to December 2023 were evaluated. A total of 70 cases were studied retrospectively. The clinical details including age, gender, sites, and dimensions were noted. The histopathological findings were evaluated and correlated with the clinical findings. Result The highest incidence was observed in the age group of 21–30 years (21.4%, 15/70) and the most commonly affected region was the head and neck region (60%, 42/70). The size of cysts ranged from 0.5 to 8 cm in diameter with a mean of 2.9 cm. The unusual sites observed in this study were 1 at the plantar aspect of the foot and 1 at the dorsal aspect of the foot. 3 cases were reported from the upper eyelid, 1 from the breast, 1 from the chest, 2 from the gluteal region, and 1 from the finger. Histopathological findings included rupture of epidermoid cysts with giant cell reaction. Conclusion Epidermoid cysts are common benign intradermal or subcutaneous tumors, but they can have unusual presentations and histopathological findings. Recommendations Epidermoid cysts need early diagnosis and treatment as they can cause cosmetic and functional impairment.